ECG Quiz no. 19 - Okreglicki, A (SA Heart Journal, 2017)
This is the ECG of a 79-year old woman with no past medical history who presents with shortness of breath at rest for 1 day. She admits to an episode of severe chest pain lasting a couple of hours the previous day. On examination she is mildly distressed, not in pain, with a BP of 90/60 and crackles in lung lower zones.